Wyrażenie „голосовать ногами / głosować nogami” we współczesnym języku rosyjskim i polskim - Miturska-Bojanowska, Jolanta; Ignatowicz-Skowrońska, Jolanta (Studia Rossica Posnaniensia, 2016)
Since the end of the 20th century, in the Russian and Polish language the phrase голосовать ногами / głosować nogami has broadened its usage and its meaning in both languages. This refers to the primal Latin phrase pedibus in sententiam ire. Its popularity could be related to the influence of the English idiom vote with your feet.